Urban Occupancy of Areas with Flood Risk and Territorial Dynamics: The Case of the Great Nador Agglomerations (Morocco) - Tribak, Abdellatif; El Amrani, Hassan (Revista de Estudios Andaluces, 2018)
Flooding in the urban environment has long been a major concern for territorial actors as well as for the local population in the Great Nador region. It affects, in a recurring way, the main urban agglomerations and the peripheral zones which surround them. Due to high population growth, a trend towards urbanization and climate change, the causes of floods are changing, and their impacts are intensifying in this area. These phenomena constitute a major obstacle for development and threaten the populations, especially in the peripheral districts which are in rapid urban expansion. This article aims to analyze and inventory the economic, social and environmental consequences of the recent flood events in Nador, while explaining the elements of an integrated approach to flood risk management in urban areas.